Pelatihan Instalasi Jaringan Komputer di SMKS 9 Muhammadiyah Kota Bengkulu Dalam Menghadapi Ujian Kompetensi siswa - Yul, Fadlul Amdhi; Siska , Jumiati; Hermawansa; Monica (Jurnal Kewirausahaan dan Bisnis, 2022)
Computer Network Engineering or commonly abbreviated as TKJ is a major in SMK that studies how to assemble computers, basic networks, and hardware components that are in computers. Apart from that, as a TKJ major, you will also learn how to install operating systems (OS), handle problems related to personal computers (PCs), create Local Area Networks (LAN) networks, design websites, and much more. prepare to be able to install computer networks, both computer networks within homes, offices, between offices, between cities, and between countries. FYI, every company needs a computer network. Usually, companies use a LAN-type computer network that functions to connect one computer to another. The result of this PKM activity is an increase in skills and knowledge in using Information Technology such as the application of computer networks to support competency exam activities.